(untitled) (Open Herald: Periodical of Methodical Research, 2023)
The problem of waste-free technology of the industry, that is, the complete and rational use of all components of milk, is present all over the world. The essence of the problem lies in the existing traditional technology for the production of dairy products.Secondary milk raw material is characterized by a unique, balanced composition and properties that differ from the original milk of the raw material. The amount of secondary milk raw material and its value deserve the attention of processors. In the dairy industry, most secondary milk raw materials, such as whey, are thrown away because it is cheaper for the producer to throw it away than to spend money on processing it. Whey is a valuable source of essential components of food, so it is rational to use it for further food and nutrition purposes. Waste-free technologies make it possible to use all components of milk for food products, medicines, feed concentrates and technical semi-finished products based on industrial processing. Thus, the chemical composition of milk whey, which is a secondary product in the production of dairy products, was analyzed. The content of proteins, lipids, lactose, mineral substances, vitamins, enzymes and organic acids in whey was studied. Their quantity, biological significance and other properties in the milk serum were analyzed